Connect - Richards, Jack C. (Cambridge University Press, 2005)
Connect is a fun, 4-level, multi-skills American English course especially written and designed for young adolescents. Connect Student's Book 2 is a high-beginning-level text for students aged 11-15 who are learning English for the first time. It develops speaking, listening, reading, and writing skills. Tasks provide opportunities for students to share their experiences. High-interest topics motivate them to learn. Student's Book 2 contains eight units divided into 2-page lessons. Also included are 8 Learning Logs or self-assessment “tests” and 8 Theme Projects